10 ps timing with highly irradiated 3D trench silicon pixel sensors. (1st January 2023) - Lampis, A.; Borgato, F.; Brundu, D.; Cardini, A.; Cossu, G.M.; Dalla Betta, G.-F.; Garau, M.; La Delfa, L.; Lai, A.; Loi, A.; Obertino, M.; Simi, G.; et al.
Abstract: In this paper the results of a beam test characterization campaign of 3D trench silicon pixel sensors are presented. A time resolution in the order of 10 ps was measured both for non-irradiated and irradiated sensors up to a fluence of 2.5 × 10 16  1 MeV neq  cm −2 . This feature and a detection efficiency close to 99% make this sensors one of the best candidates for 4D tracking detectors in High-Energy-Physics experiments.